Revisiting the public debt stability condition: Rethinking the Domar condition - Naoyuki Yoshino; Hiroaki Miyamoto (Asian Development Bank Institute (ADBI), 2020)
This paper revisits the fiscal sustainability condition proposed by Domar (1944). The Domar condition is derived from the government budget constraint and thus focuses on the supply side of the government bond. By considering the demand for the government bond, this paper finds that public debt sustainability depends on interest rate sensitivity to changes in government bond supply and demand. Data shows that the prediction of our model on public debt sustainability is consistent with the cases of Greece and Japan.
Keywords: E12; E62; H63; 330; Domar condition; fiscal sustainability; demand for government bonds